2024
DOI: 10.3390/polym16010141
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Properties, Strength, and Durability of Fiber-Reinforced Geopolymer and Conventional Concrete: A Review

Osama Mohamed,
Haya Zuaiter

Abstract: Reducing the environmental footprint of the construction industry in general and concrete in particular is essential. The addition of synthetic and natural fibers to concrete mixes at appropriate dosages enhances durability and strength and extends the lifespan of concrete infrastructures. This study reviews the geometric and mechanical properties of selected fibers such as steel, basalt, polypropylene, polyvinyl alcohol, polyethylene, glass, carbon, and natural fibers and their impact on concrete fresh, mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 129 publications
1
5
0
Order By: Relevance
“…The optimal amount of fibers in the geopolymer matrix makes it possible to obtain a composite with higher compressive and flexural strength. However, an excessive amount of BF in this case, 2% or more, leads to poor compaction and increased porosity, which will reduce the strength properties [60]. The positive effect of basalt fiber at optimal dosages on the strength characteristics of geopolymer composites is also confirmed by a number of the following studies [57,58,64,65].…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The optimal amount of fibers in the geopolymer matrix makes it possible to obtain a composite with higher compressive and flexural strength. However, an excessive amount of BF in this case, 2% or more, leads to poor compaction and increased porosity, which will reduce the strength properties [60]. The positive effect of basalt fiber at optimal dosages on the strength characteristics of geopolymer composites is also confirmed by a number of the following studies [57,58,64,65].…”
Section: Resultsmentioning
confidence: 74%
“…It can be concluded that changing the molarity of NaOH solution from 8 M to 14 M in the alkaline activator does not significantly affect the density of geopolymer mixtures, but does affect their workability, reducing cone settlement. This is due to the fact that higher concentrations of sodium hydroxide solution accelerate the setting process of fresh geopolymer concrete and increase its viscosity, while reducing workability parameters [60]. For example, in [61], self-compacting concrete mixtures with a higher content of sodium hydroxide (12 M) showed lower fluidity than mixtures where an activator with a lower content of sodium hydroxide (8 M) was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the traditional granular fuels made by molding technology has low quality, and various pollutants are released during the combustion process [ 3 , 4 ]. Consequently, selecting suitable additives is a crucial solution to improve the quality of granular fuels and reduce power consumption during granularizing processes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete is a widely selected construction material because of its higher compressive strength, excellent durability, and ease of use [ 1 , 2 , 3 , 4 ]. Nevertheless, concrete is also subject to freeze–thaw damage, which can significantly reduce its mechanical properties and lead to premature failure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%